Community Structure and Macroalgae Diversity in Peh Pulo Beach, Blitar Regency - Marinda Sari Sofiyana; Mar’atus Sholihah; Dewi Setyaningsih (Al-Hayat: Journal of Biology and Applied Biology, 2023)
The coastal area of Peh Pulo Beach, located in the Blitar Regency, has a high potential for biodiversity, including macroalgae. This research aims to understand the community structure and diversity of macroalgae at Peh Pulo Beach. The sampling was conducted on August 2023 using the 1 x 1 m quadrant transect method. Macroalgae were collected at three observation stations, with three plots observed at each station. Abiotic environmental parameters measured included temperature, salinity, pH, light intensity, and substrate. The results of macroalgae identification at Peh Pulo Beach reveal 21 species belonging to 16 genera and 14 families. These species were classified into Chlorophyta (9 species), Phaeophyta (4 species), and Rhodophyta (8 species). The Shannon Diversity Index value obtained is 2.84, indicating that the macroalgae diversity along the coast of Peh Pulo falls under the moderate category.